2018
DOI: 10.1002/bjs.10655
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon volume and prognosis of patients with advanced papillary thyroid cancer and lateral nodal metastasis

Abstract: Surgeon volume is associated with structural recurrence, but not distant metastasis or cancer-specific death in patients with N1b PTC. Surgeon volume is important in initial surgery for advanced PTC with extensive nodal metastasis in order to ensure curative outcome and reduce treatment-related morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 38 publications
2
26
0
1
Order By: Relevance
“…More prevalent detection of TC has increased the frequency of thyroid surgery and has led to the production of competent, high-volume surgeons in the tertiary care centers. In our previous study, the prognosis of advanced TC performed by high-volume surgeons was better than that performed by low-volume surgeons 27 . Our data showed that, after 2004, neck dissection was significantly performed more than prior to 2004.…”
Section: Discussionmentioning
confidence: 78%
“…More prevalent detection of TC has increased the frequency of thyroid surgery and has led to the production of competent, high-volume surgeons in the tertiary care centers. In our previous study, the prognosis of advanced TC performed by high-volume surgeons was better than that performed by low-volume surgeons 27 . Our data showed that, after 2004, neck dissection was significantly performed more than prior to 2004.…”
Section: Discussionmentioning
confidence: 78%
“…The prognosis of papillary thyroid carcinoma is good. 10year survival rate more is than 90%, especially in young patients (98%) [12][13][14][15][16][17]. The factors affecting the prognosis included vascular invasion, nuclear atypia, tumor size and age.…”
Section: Resultsmentioning
confidence: 99%
“…Although the surgical approach is the most important for the WDTC treatment, the question concerning the surgical intervention volume and long-term treatment results, in particular the patients survival, remains poorly studied. There are even the data refusing the interactions between the surgical intervention volume and the level of WDTC patient's survival: this interaction is underlined to be important only in cases of primary operations on great metastasizing tumors [22]. The majority of surgeons think the gland extirpation together with its tumor is a satisfactory volume of intervention in cases of small carcinomas which do not metastasize and do not invade to extrathyroid tissues (category Т1N0М0); it explains the excellent prognosis for the patient cohort having survived the same operation (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…in cases of more aggressive carcinomas (Table 3). Therefore, we cannot share the idea that the volume and type of surgical intervention do not exert on the level of patients survival [22].…”
Section: Groupsmentioning
confidence: 97%